Synovial fluid niche promoted differentiation of dental follicle mesenchymal stem cells toward chondrogenesis in rheumatoid arthritis - Deniz Genç,; Merve Sezer Kürkçü,; Gürkan Yiğittürk,; Burcu Günaydın,; Hülya Elbe,; Akın Aladağ,; Bekir Çöl,; Emine Figen Tarhan, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to investigate the differentiation potential of dental follicle mesenchymal stem cells (MSCs) in the synovial fluid (SF) niche of early-onset or end-stage rheumatoid arthritis (RA). Patients and methods: Between May 2020 and January 2021, six patients (1 male, 5 females; mean age: 57.5±11.2 years; range, 49 to 65 years) who were diagnosed with RA with the indication of SF aspiration were included in the study. The third passage dental follicle stem cells (DFSCs) were cocultured with fresh SF samples of end-stage or early-onset RA patients in micromass culture system for 21 days. SF samples were analyzed for secreted cytokines. Chondrogenic markers (CD49e, CD49f) were analyzed in DFSCs, gene expression analysis was performed for the expressions of Col I, Col II, Aggrecan and Sox-9, and histochemical analysis was performed by staining three-dimensional pellets with anti-collagen II antibody. The neutralization assay was performed with anti-interleukin (IL)-6, anti-interferon-gamma (IFN-g), and anti-IL-1beta(b). Results: The high levels of IL-1b and IL-6 were observed in end-stage RA patients’ SF samples compared to the early-onset patients (p<0.05). The CD49e and CD49f expressions in DFSCs were significantly higher in the SF samples of end-stage RA patients (p<0.05). Also, the Col II, Sox-9 and Aggrecan messenger ribonucleic acid (mRNA) expressions increased in the DFSCs, when cultured with end-stage RA patients’ SF samples (p<0.01). Collagen-II expression in histochemical analysis of micromass pellets was higher in the DFSCs cultured with end-stage RA patients’ SF samples. The neutralization of IL-6 significantly decreased the CD49e and CD49f expressions (p<0.05). Conclusion: The high levels of IL-6 in SF niche of end-stage RA patients were found to differentiate DFSCs toward chondrogenesis. Based on these findings, DFSCs can be used as a new cell-based treatment in RA patients for the cartilage damage.